Ethos discursif et identités citoyennes dans la presse française pendant la pandémie du Covid-19 à travers les éditoriaux du quotidien Le Monde - Ráčková, Lucia; Schmitt, Francois (Studia Romanica Posnaniensia, 2024)
The ethos of the journalist is based on his representations of the public space. Updated in the discourse, they participate in the construction of citizen identity. This is what we show through an enunciative analysis of editorials from the daily “Le Monde” during the Covid-19 pandemic crisis. The analysis highlights an increasingly marked identity divide during the crisis.